Efficiency of CFRP NSM strips and EBR plates for flexural strengthening of RC beams and loading pattern influence. (June 2015) - Bilotta, Antonio; Ceroni, Francesca; Nigro, Emidio; Pecce, Marisa
Abstract: The efficiency of Fibre Reinforced Polymer (FRP) materials for strengthening existing Reinforced Concrete (RC) structures according to the Near Surface Mounted (NSM) technique can be greater than the External Bonded Reinforcement (EBR) technique because debonding phenomena are less relevant and thus the tensile strength of the FRP materials is better exploited. Some experimental results and numerical analyses performed in the past showed that the debonding load in RC beams reinforced with EBR-FRP could be influenced by the effect of the loading pattern. Nevertheless, most bending tests available in the literature have been conducted with a 3 or 4 point loading scheme and very few tests have been performed under distributed loads. This issue has not yet been investigated for RC beams reinforced with NSM-FRP. Therefore, the results of flexural tests on RC beams strengthened with both NSM and EBR techniques are discussed in this paper to show that the debonding phenomena for NSM strip strengthened beams are less significant than for EBR plate beams. Moreover, the effect of the loading pattern is analysed to evaluate the sensitivity of failure modes and loads to different distributions of bending moment and shear along the beam. Finally, the experimental results are compared with the predictions of theoretical models and code provisions.